2018
DOI: 10.1016/j.jmbbm.2018.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue behavior and surface characterization of a Y-TZP after laboratory grinding and regeneration firing

Abstract: This study evaluated the effect of grinding and regeneration firing on the flexural fatigue limit and surface characterization of Lava™ Y-TZP ceramic. Forty bar-shaped specimens with 20 × 4.0 × 1.2 mm constituted the as-sintered group (AS = control group), and 80 specimens with 20 × 4.0 × 1.5 mm were ground with cylindrical laboratory stone under water-cooling (WG) or in a dry condition (G) to reach 1.2 mm in thickness. Half of specimens were submitted to regeneration firing (1000 °C, 30 min), forming the grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 53 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…However, the term “partially” stabilized zirconia (PSZ) refers to lower concentrations of Y2O3 between 4 and 6 mol%. In order to achieve high translucency of yttria‐stabilized polycrystal zirconia (Y‐TZP), the aluminum content is lowered and the yttria content is increased in order to minimize the low‐temperature degradation of the material 3‐7 …”
Section: Introductionmentioning
confidence: 99%
“…However, the term “partially” stabilized zirconia (PSZ) refers to lower concentrations of Y2O3 between 4 and 6 mol%. In order to achieve high translucency of yttria‐stabilized polycrystal zirconia (Y‐TZP), the aluminum content is lowered and the yttria content is increased in order to minimize the low‐temperature degradation of the material 3‐7 …”
Section: Introductionmentioning
confidence: 99%
“…After the HT, a total reversal of m→t phase was observed for both the treatment of 900°C/1 h (C9 and G9) and 1000°C/30 min (C10 and G10). This behavior had already been observed for the conventional zirconia, 25,34,35 but not for the monolithic zirconia. It was observed that the heat treatment was able to maintain the direction of the transformation phases m→t→c, converting the monoclinic phase into tetragonal and tetragonal into cubic, returning the material to its initial conformation.…”
Section: Discussionmentioning
confidence: 68%